2018
DOI: 10.21608/ejabf.2018.8768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a plant product (Thymol) on the salivary gland of the giant slug Limax maximus in Egypt (Histological and Ultrastructural study)

Abstract: Thymol monotrpenoid compound is naturally found in many plants. It exhibites molluscicial activity against the land snails and slugs. The present study aims to describe histological, histochemical and ultrastructural investigations to display and clarify any deleterious effects probably evoked post-thymol application in the salivary gland of Limax maximus. To achieve the intended goal in this respect, the slugs were divided into three groups; the first group served as control, the second and the third groups r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…In addition, Sharaf, et al (2015) observed additional histological changes in the digestive gland of treated land snail H. vestalis with methiocarb and chlorpyrifos-pesticides included; severe tubular disruption, nuclear pyknosis and necrosis of tubules. Moreover, Mustafa (2018) reinforced the present results in another gland, salivary gland, where he found vacuolated cytoplasm and degenerated nuclei after treated with LC 90 of thymol against L. maximus.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, Sharaf, et al (2015) observed additional histological changes in the digestive gland of treated land snail H. vestalis with methiocarb and chlorpyrifos-pesticides included; severe tubular disruption, nuclear pyknosis and necrosis of tubules. Moreover, Mustafa (2018) reinforced the present results in another gland, salivary gland, where he found vacuolated cytoplasm and degenerated nuclei after treated with LC 90 of thymol against L. maximus.…”
Section: Discussionsupporting
confidence: 88%